Women working as prostitutes in Río Gallegos. A proposal from the cultural analysis - Behrens, Romina Alejandra (2017)
From the proposal of cultural analysis and discussing about hegemonic processes, the article focuses on the debate on prostitution as exploitation or a job as a result of the arrival of the abolitionist boom through its political legal form in 2008. We focus the knowledge and practices that are under dispute in Río Gallegos, in the south of Argentina, with a focus on the negotiation processes in which women who engage in prostitution participate. The final questions are related to the conditions for the collective organization of these women and how subalternity is lived in a peripheral southern enclave of the national context.